Dissecting the regulatory network of transcription factors in T cell phenotype/functioning during GVHD and GVT - Harris, Rebecca; Karimi, Mobin (Frontiers in Immunology, 2023)
Transcription factors play a major role in regulation and orchestration of immune responses. The immunological context of the response can alter the regulatory networks required for proper functioning. While these networks have been well-studied in canonical immune contexts like infection, the transcription factor landscape during alloactivation remains unclear. This review addresses how transcription factors contribute to the functioning of mature alloactivated T cells. This review will also examine how these factors form a regulatory network to control alloresponses, with a focus specifically on those factors expressed by and controlling activity of T cells of the various subsets involved in graft-versus-host disease (GVHD) and graft-versus-tumor (GVT) responses.